2019
DOI: 10.29390/cjrt-2019-011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an extubation readiness test protocol at a tertiary care fully outborn neonatal intensive care unit

Abstract: Background and objectivesExtubation readiness testing (ERT) in the Neonatal Intensive Care Unit (NICU) is highly variable and lacking standardized criteria. To address this gap, an evidence-based, inter-professionally developed ERT protocol was implemented to assess effectiveness on extubation failure within 72 h and on duration of intubation (DOI).MethodsA longitudinal retrospective chart review in a level III, fully outborn NICU, of intubated infants admitted 1-year prior (Group 1), and 1 year after implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…11,[17][18][19][20] A recent study reported that the implementation of a 2-step extubation readiness test, which included a 3-min SBT, in a cohort of moderate to late preterm and term infants harmonized extubation practices while also reducing extubation failure rates; however, it was unclear whether it was the specific use of an SBT or the implementation of a respiratory therapist-driven protocol that conferred the greatest benefits. 16 The use of our SBT protocol had some effect on weaning success as only 5 of the 70 preterm infants failed their first SBT attempt. However, at the time of the first SBT, infants had been ventilated for a long period (median 14 d), were considerably mature, and had an average weight of nearly 2 kg.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…11,[17][18][19][20] A recent study reported that the implementation of a 2-step extubation readiness test, which included a 3-min SBT, in a cohort of moderate to late preterm and term infants harmonized extubation practices while also reducing extubation failure rates; however, it was unclear whether it was the specific use of an SBT or the implementation of a respiratory therapist-driven protocol that conferred the greatest benefits. 16 The use of our SBT protocol had some effect on weaning success as only 5 of the 70 preterm infants failed their first SBT attempt. However, at the time of the first SBT, infants had been ventilated for a long period (median 14 d), were considerably mature, and had an average weight of nearly 2 kg.…”
Section: Discussionmentioning
confidence: 96%
“…Neonatologists around the world have increasingly adopted the practice of performing SBTs in preterm infants, despite the limited evidence guiding its use in this population. 6,12,13,16 Clinicians endorsing SBTs have typically justified practice based on a standardized assessment of extubation readiness (ie, to reduce clinical practice variations), identification of an infant's potential for extubation as early as possible (ie, to reduce unnecessary exposure to mechanical ventilation), and the ability to accurately identify infants who will fail extubation and thus prevent them from being extubated. To achieve the latter goal, the SBT is intentionally designed to impose a certain level of physiological stress on the patient to differentiate between infants capable of tolerating extubation and those who will not tolerate extubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a quality improvement (QI) initiative, Eissa et al 6 found that the use of an extubation bundle with specific components, for preterm infants 30 weeks or less of gestation, could result in successful extubation. With use of an extubation protocol, Mandhari et al 7 found that a 2-stage extubation readiness testing protocol was statistically significant in its effectiveness to reduce extubation failure rate, without increasing days of intubation, in preterm infants 32 6 / 7 weeks or less of gestation. Both Eissa et al 6 and Mandhari et al 7 had large sample sizes to ultimately show improved extubation success through the use of a bundle or algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 8 Nevertheless, one-third of neonatal intensive care units (NICUs) have reported the use of ETT-CPAP trials, conducted in various ways, as part of their extubation readiness assessment in extremely preterm infants. 4 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%